If tan α = 3 − 1 3 + 1 , then the expression cos 2 α + ( 2 + 3 ) sin 2 α
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
t g ( α ) = 2 + 3 . Therefore c o s ( 2 α ) + ( 2 + 3 ) s i n ( 2 α ) = c o s 2 ( α ) − s i n 2 ( α ) + c o s ( α ) s i n ( α ) ⋅ 2 s e n ( α ) c o s ( α ) = c o s 2 + s i n 2 = 1
For my convinience I would be taking 'alpha' as 'x',
After rationalising the given term,
tan x = 2 + (3)^0.5
sin x =[2 + (3)^0.5]cos x
Now the expression whose value we need to find,
cos 2x + (2 + (3)^0.5)sin 2x
cos^2 x - sin^2 +(2)[2 + (3)^0.5]cos x . sin x
cos^2 x - sin^2 x + 2 sin x . sin x
cos^2 x - sin^2 + 2sin^2 x
cos^2 x + sin^2 x = 1
Based on the given information tan α , create a triangle of sides length 3 + 1 and 3 − 1 . Thus, the hypotenuse of the triangle, after calculating with Pythagoras theorem, is 8 . Now the values of sin α , cos α and tan α can be calculated simply by referring to this triangle (which you have hopefully ingrained in your head by now).
cos 2 α can be calculated with:
cos 2 α = cos 2 α − sin 2 α = 8 4 − 2 3 − 8 4 + 2 3 = − 2 3
sin 2 α can be calculated with:
sin 2 α = 2 sin α cos α = 2 ( 8 3 + 1 ) ( 8 3 − 1 ) = 2 1
After substituting the values into the expression and simplifying it, you are left with 1 .
Problem Loading...
Note Loading...
Set Loading...
Let t = tan α = 3 − 1 3 + 1 = ( 3 − 1 ) ( 3 + 1 ) ( 3 + 1 ) 2 = 2 4 + 2 3 = 2 + 3
cos 2 α + ( 2 + 3 ) sin 2 α = 1 + t 2 1 − t 2 + t ˙ 1 + t 2 2 t = 1 + t 2 1 + t 2 = 1